Characterization of the Fungitoxic Activity on Botrytis Cinerea of N-Phenyl-Driman-9-Carboxamides - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Castro-Valenzuela, P; Castro-Valenzuela, P; Navarro-Gajardo, F; Navarro-Gajardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
A total of 12 compounds were synthesized from the natural sesquiterpene (-) drimenol (compounds 4 to 15). The synthesized compounds corresponded to N-phenyl-driman-9-carboxamide derivatives, similar to some fungicides that inhibit the electron-transport chain. Their structures were characterized and confirmed by1H NMR,13C NMR spectroscopy, and mass spectrometry. Compounds 5 to 15 corresponded to novel compounds. The effect of the compounds on the mycelial growth of Botrytis cinerea was evaluated. Methoxylated and chlorinated compounds in the aromatic ring (compounds 6, 7, 12, and 13) exhibited the highest antifungal activity with IC50 values between 0.20 and 0.26 mM. On the other hand, the effect on conidial germination of B. cinerea of one methoxylated compound (6) and one chlorinated compound (7) was analyzed, and no inhibition was observed. Additionally, compound 7 decreased 36% the rate of oxygen consumption by germinating conidia. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).